An atorvastatin calcium and poly(L-lactide-co-caprolactone) core-shell nanofiber-covered stent to treat aneurysms and promote reendothelialization. (15th July 2020) - Chu, Jin; Chen, Li; Mo, Zengshuo; Bowlin, Gary L; Minden-Birkenmaier, Benjamin A.; Morsi, Yosry; Aldalbahi, Ali; El-Newehy, Mohamed; Wang, Wu; Mo, Xiumei
Abstract: Aneurysmal subarachnoid hemorrhage is a common complication caused by an intracranial aneurysm that can lead to hemorrhagic stroke, brain damage, and death. Knowing this clinical situation, the purpose of this study was to develop a controlled-release stent covered with a core-shell nanofiber mesh, fabricated by emulsion electrospinning, for the treatment of aneurysms. By encapsulating atorvastatin calcium (AtvCa) in the inner of poly (L-lactide-co-caprolactone) (PLCL) nanofibers, the release period of AtvCa was effectively extended. The morphology and inner structure of the core-shell nanofibers were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), respectively. The release of AtvCa from the nanofiber system continued for more than ten weeks without a significant initial burst release. The nanofiber mesh structure degraded gradually but maintained its fiber morphology before neovascularization. The results of this study further elucidated the reendothelialization mechanism of AtvCa by analyzing the nitric oxide (NO) expression from seeded HUVECs. The in vivo studies demonstrated that the PLCL-AtvCa covered stents were capable of separating the aneurysm dome from the blood circulation, leading to the abolishment of the aneurysm. Moreover, the AtvCa controlled release promoted the in vitro proliferation of HUVECs on the nanofiber meshes, and the PLCL-AtvCa covered stents induced in vivo neovascularization. Statement of Significance: Intracranial aneurysms are pathological dilatations of blood vessels that have developed an abnormally weak wall structure, thus prone to rupture. Covered stents had been demonstrated to be a method for the treatment of intracranial aneurysm. We prepared a controlled-release stent covered with a core-shell nanofiber mesh, fabricated by emulsion electrospinning, which encapsulated atorvastatin calcium in the inner portion of nanofibers. The results of this study further elucidated the reendothelialization mechanism of AtvCa by analyzing the nitric oxide (NO) expression from seeded HUVECs. The generated AtvCa-load covered stents separated the aneurysm dome from the blood circulation, and keep long-term patency of the parent artery. But also induced neovascularization, thus provide further protection against recurrence of aneurysms after nanofiber meshes degradation. Graphical abstract: Image, graphical abstract